Relevansi Dimensi Pembangunan Ekonomi Berkelanjutan (SDGs) dalam Perspektif Ekonomi Ibnu Khaldun - Muchlisin, Muchammad Chafidz; Mugiyati, Mugiyati (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
This research discusses the relevance of the dimensions of Sustainable Economic Development (SDGs) in the perspective of Ibn Khaldun's economic thought. The background of this research is the need for an in-depth study of the relationship between classical thinking in Islamic economics and sustainable economic development targets represented by the SDGs so as to provide social and economic welfare for the community. The research method used is a literature study, which involves reviewing literature from books, journal articles, and relevant documents, and using a descriptive analysis approach to Ibn Khaldun's economic thought and its relationship to the pillars of economic development of the SDGs. With the aim of assessing the extent to which the economic concepts proposed by Ibn Khaldun, such as national wealth, economic equilibrium, wage theory, national trade, taxes, and market mechanisms, are relevant to the achievement of the SDGs. The results show that Ibn Khaldun's economic thought is very relevant to several key aspects of the SDGs, such as equitable distribution of wealth, sustainable management of natural resources, and the role of the state in maintaining economic justice and social welfare. Ibn Khaldun's concepts provide the basis for inclusive and sustainable economic development in accordance with the goals of the SDGs, especially in creating decent jobs, reducing inequality, and ensuring balance in the market mechanism.